Direct access to benzo[b]fluorenes via a gold-catalysed A3-coupling strategy - Lustosa, Danilo Machado; Cieslik, Patrick; Schüle, Deborah Katharina; Bruckhoff, Tim; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic chemistry frontiers, 2019)
A one-pot atom- and step-economical method for the synthesis of benzo[b]fluorenes, from aldehydes, alkynes and amines, proceeding via an A3-coupling/formal [4 + 2] thermal cyclization is described. The transformation generates water as the only by-product and three new carbon-carbon bonds are simultaneously formed. The scope was demonstrated by the synthesis of 32 benzo[b]fluorenes and, by specific designing of starting materials, regiocontrol could be accessed for some substrates.
Die Ziffer "3" im Titel ist hochgestellt
Gesehen am 24.06.2019